ADEQUACY LEVELS OF MACRO NUTRIENTS ON BADMINTON PLAYERS FITNESS - Ahmad Hariyanto (Bajang Institute, 2023)
Adequate protein intake is essential for health and well-being at all ages. In children, adequate protein intake is essential for growth and development. In adults, adequate protein intake helps maintain lean body mass and prevents age-related loss of skeletal muscle mass. An athlete is required to always maintain physical fitness. Fitness is one indicator to determine a person's level of health, especially for an athlete. The fitter a person is, the healthier that person is. This study aims to analyze the relationship between adequate levels of macronutrients and fitness in badminton athletes. This research uses a quantitative type of research with a cross-sectional research design and a sample of 32 athletes. Data was obtained via online Google form, namely data on carbohydrate, protein and fat intake with 3x24 hour food records via the IPAQ questionnaire sheet. Data analysis used the Spearman Rank Correlation test. as many as 28 (87.5%) respondents had insufficient levels of carbohydrate sufficiency, and as many as 31 (96.9%) respondents had sufficient levels of protein which was more as well as adequate levels of fat. 31 (96.9%) respondents had sufficient levels of fat. which is excessive. And it is known that as many as 25 (78.1%) respondents were fit. There was no significant relationship with all research variables (p≥0.05). The conclusion of this study shows that there is no relationship between adequate levels of carbohydrates, adequate levels of protein, adequate levels of fat on athlete fitness (p ≥ 0.05). There is no significant relationship between the level of macronutrient adequacy and the fitness of badminton athletes